Outcomes after tricuspid valve surgery concomitant with left ventricular assist device implantation in the EUROMACS registry: a propensity score matched analysis. (18th July 2019) - Veen, Kevin M; Caliskan, Kadir; de By, Theo M M H; Mokhles, Mostafa M; Soliman, Osama I; Mohacsi, Paul; Schoenrath, Felix; Gummert, Jan; Paluszkiewicz, Lech; Netuka, Ivan; Loforte, Antonio; Pya, Yuriy; et al.
Abstract: OBJECTIVES: Tricuspid regurgitation (TR) is common in patients receiving a left ventricular assist device (LVAD). Controversy exists as to whether concomitant tricuspid valve surgery (TVS) is beneficial in currently treated patients. Therefore, our goal was to investigate the effect of TVS concomitant with a LVAD implant. METHODS: The European Registry for Patients with Mechanical Circulatory Support was used to identify adult patients. Matched patients with and without concomitant TVS were compared using a propensity score matching strategy. RESULTS: In total, 3323 patients underwent LVAD implantation of which 299 (9%) had TVS. After matching, 258 patients without TVS were matched to 258 patients with TVS. In the matched population, hospital deaths, days on inotropic support, temporary right ventricular assist device implants and hospital stay were comparable, whereas stay in the intensive care unit was higher in the TVS cohort (11 vs 15 days; P = 0.026). Late deaths ( P = 0.17), cumulative incidence of unexpected hospital readmission ( P = 0.15) and right heart failure ( P = 0.55) were comparable between patients with and without concomitant TVS. In the matched population, probability of moderate-to-severe TR immediately after surgery was lower in patients with concomitant TVS compared to patients without TVS (33% vs 70%; P = 0.001). Nevertheless, the probability of moderate-to-severe TR decreased more quickly in patients without TVS ( P = 0.030), resulting in comparable probabilities of moderate-to-severe TR within 1.5 years of follow-up. CONCLUSIONS: In matched patients, TVS concomitant with LVAD implant does not seem to be associated with better clinical outcomes. Concomitant TVS reduced TR significantly early after LVAD implant; however, differences in probability of TR disappeared during the follow-up period.